Cēramāṉ Perumāṇāyaṉār aruḷicceyta Poṉvaṇṇattantāti mūlamum, Kā. Poṉṉucāmi Nāṭṭār iyaṟṟiya uraiyum - Cēramāṉ Perumāḷ Nāyaṉār, 9th cent (SAMP early 20th-century Indian books project, 1935)
Hymns in praise of Śiva, Hindu deity; with commentary.